2016
DOI: 10.1016/j.toxlet.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhibition kinetics of several organophosphates, including some nerve agent surrogates, using human erythrocyte and rat and mouse brain acetylcholinesterase

Abstract: Because testing of nerve agents is limited to only authorized facilities, our laboratory developed several surrogates that resemble nerve agents because they phosphylate the acetylcholinesterase (AChE) with the same moiety as the actual nerve agents. The inhibition kinetic parameters were determined for AChE by surrogates of cyclosarin (NCMP), sarin (NIMP, PIMP and TIMP) and VX (NEMP and TEMP) and other organophosphorus compounds derived from insecticides. All compounds were tested with rat brain and a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…HuAChE or huBChE were treated with F-VX-surrogate (from 10 to 160 nM) to > 95% inhibition and the recovery of enzyme activity measured following dilution to halt further inhibition or possible re-inhibition. The spontaneous reactivation rate constants ( k r ) for were9.31 × 10 −5 min −1 (t ½ = 124 h; HuAChE) and 1.13 × 10 −4 min −1 (t ½ = 102 h; HuBChE), which data is in general agreement with k r rates found for VX and the p -nitrophenoxy VX surrogates (Albuquerque et al, 2006; Coban et al, 2016; Kuca et al, 2010a; Sidell and Groff, 1974). The data implies that ChE-OP(O)(CH 3 )(OCH 2 CH 2 F) adducts are stable and likely measurable in vivo as the corresponding [ 18 F]containing OP-AChE adduct over the lifetime of the tracer, although the lack of restoration of enzyme activity cannot be attributed solely to the ChE-OP(O)(CH 3 )(OCH 2 CH 2 F) adduct.…”
Section: F-vx Surrogate: O-(2-[18f]fluoroethyl)-o-(p-nitrophenyl) Msupporting
confidence: 81%
See 1 more Smart Citation
“…HuAChE or huBChE were treated with F-VX-surrogate (from 10 to 160 nM) to > 95% inhibition and the recovery of enzyme activity measured following dilution to halt further inhibition or possible re-inhibition. The spontaneous reactivation rate constants ( k r ) for were9.31 × 10 −5 min −1 (t ½ = 124 h; HuAChE) and 1.13 × 10 −4 min −1 (t ½ = 102 h; HuBChE), which data is in general agreement with k r rates found for VX and the p -nitrophenoxy VX surrogates (Albuquerque et al, 2006; Coban et al, 2016; Kuca et al, 2010a; Sidell and Groff, 1974). The data implies that ChE-OP(O)(CH 3 )(OCH 2 CH 2 F) adducts are stable and likely measurable in vivo as the corresponding [ 18 F]containing OP-AChE adduct over the lifetime of the tracer, although the lack of restoration of enzyme activity cannot be attributed solely to the ChE-OP(O)(CH 3 )(OCH 2 CH 2 F) adduct.…”
Section: F-vx Surrogate: O-(2-[18f]fluoroethyl)-o-(p-nitrophenyl) Msupporting
confidence: 81%
“…The bimolecular inhibition rate constants ( k i ) were determined for electric eel (EEAChE) k i = 4.2 × 10 6 M −1 min −1 , recombinant human AChE k i = 1.1 × 10 7 M −1 min −1 , recombinant human butyrylcholinesterase (HuBChE) k i = 1.95 × 10 5 M −1 min −1 and rat brain AChE k i = 6.1 × 10 6 M −1 min −1 indicating that the F-VX surrogate is a potent, in vitro inhibitor and 5-fold more potent than paraoxon against rat brain AChE. (Johnson and Wallace, 1987) Work by Chambers (Coban et al, 2016; Meek et al, 2012) also showed that (Me)(EtO)P(O)(OPNP) was a strong inhibitor ( k i = 10 5 M −1 min −1 ) of acetyl- and butyrylcholinesterases matching the mechanism of VX inhibition. The k i values and likelihood of the PNP acting as leaving group strongly suggests that the mechanism of AChE inhibition proceeds via formation of the (2-fluoroethyl) methylphosphonate (Scheme 5) that would by analogy, afford 18 [F]-labeled enzyme from F-VX surrogate.…”
Section: F-vx Surrogate: O-(2-[18f]fluoroethyl)-o-(p-nitrophenyl) Mmentioning
confidence: 99%
“…30,31 We have also successfully employed nerve agents surrogates using the described methodology. [32][33][34]…”
Section: Reactivation Of Cholinesterasementioning
confidence: 99%
“…Given these common structural components, we developed a hybrid OP structure based upon the nerve agent VX and paraoxon (insecticide oxon) modified to incorporate an [ 18 F]fluorine atom to produce an OP‐based PET imaging tracer (Figure ). The resultant fluoro‐VX surrogate, O‐(2‐fluoroethyl)‐O‐( p ‐nitrophenyl) methylphosphonate, uses a p ‐nitrophenoxy leaving group and acts similarly in vitro and in vivo to VX without handling concerns . The fluorine tracer atom is strategically positioned 4 bonds from the reactive phosphorus atom to minimize steric or electronic perturbation .…”
Section: Introductionmentioning
confidence: 99%
“…The resultant fluoro-VX surrogate, O-(2fluoroethyl)-O-(p-nitrophenyl) methylphosphonate, uses a p-nitrophenoxy leaving group and acts similarly in vitro and in vivo to VX without handling concerns. 6,7 The fluorine tracer atom is strategically positioned 4 bonds from the reactive phosphorus atom to minimize steric or electronic perturbation. 8 Injection of high specific activity O-(2-[ 18 F] fluoroethyl)-O-(p-nitrophenyl) methylphosphonate, [ 18 F]1, in rats shows localization of radioactivity in AChE-rich regions of brain and other tissues 5 where it likely exists as (CH 3 )( 18 FCH 2 CH 2 O)P(O)-AChE and other esterase adducts.…”
Section: Introductionmentioning
confidence: 99%